Tackling sexual violence at universities : an international perspective - Towl, Graham J.; Walker, Tammi (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"This is the only book to offer an international perspective on the incidence, reporting and impact of sexual violence at universities. Drawing on evidence from the UK, North America and Australia, it situates sexual violence in universities within a broader societal context, and argues that university communities are uniquely well placed to prevent sexual violence, as well as support those who report it. Examining both the psychological and structural challenges to reporting sexual violence, the book provides a set of recommendations that move beyond awareness campaigns to call for systems to be put in place whereby reports of sexual assault are handled promptly, fairly, and consistently"--
Tackling sexual violence at universities; themes and perspectives -- What do we know about sexual violence? -- Tackling sexual violence at universities in the UK -- Sexual violence on us campuses -- Sexual violence at Australian universities -- Canadian universities and sexual violence -- Reflections on responding to sexual violence in European universities -- Tackling sexual violence and misconduct; what do universities in the UK need to do?.
OCLC-licensed vendor bibliographic record.
Keywords: Rape in universities and colleges -- Prevention -- Cross-cultural studies; Rape in universities and colleges -- Psychological aspects -- Cross-cultural studies; Education and state -- Cross-cultural studies; EDUCATION / Administration / General; EDUCATION / Organizations & Institutions; PSYCHOLOGY / General; PSYCHOLOGY / Applied Psychology